Analisis Perbandingan Kinerja Keuangan Perusahaan Manufaktur Sub Sektor Pakan Ternak di Indonesia: Studi pada PT Chareoen Pokphand TBK, PT Japfa Comfeed TBK, dan PT Malindo Feedmill TBK Periode 2019-2023 - Maftuhin Agung Prasetia; Moch Iqbal Romadhan; Dicky Satria Ananta Haqq; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the comparative financial performance of manufacturing companies in the livestock feed sub-sector in Indonesia, specifically PT Charoen Pokphand Indonesia Tbk, PT Japfa Comfeed Indonesia Tbk, and PT Malindo Feedmill Tbk, during the 2019-2023 period. The research employs a descriptive quantitative analysis method using annual financial report data published by each company. Financial ratios, such as profitability, liquidity, solvency, and operational efficiency ratios, are the primary indicators used to assess financial performance.The findings reveal significant differences in the financial performance of the three companies. PT Charoen Pokphand Indonesia Tbk demonstrates excellence in profitability ratios, with consistently high net profit margins, while PT Japfa Comfeed Indonesia Tbk excels in operational efficiency. On the other hand, PT Malindo Feedmill Tbk faces challenges in maintaining solvency ratio stability. External factors, such as fluctuations in raw material prices and domestic market dynamics, also influence each company's financial performance.This study provides valuable insights for stakeholders to understand the financial conditions of the livestock feed industry in Indonesia and serves as a reference for strategic decision-making to enhance competitiveness in the market.